Temporal dynamics and genetic control of transcription in the human prefrontal cortex - Colantuoni, Carlo; Lipska, Barbara K.; Ye, Tianzhang; Hyde, Thomas M.; Tao, Ran; Leek, Jeffrey T.; Colantuoni, Elizabeth A.; Elkahloun, Abdel G.; Herman, Mary M.; Weinberger, Daniel R.; Kleinman, Joel E. (Nature (London), 2011)
Gene expression in the human brain Gene expression controls and dictates everything from development and plasticity to ongoing neurogenesis in the brain, yet the temporal dynamics of transcription throughout the brain's lifetime have been mostly unknown. Here, two groups present a large gene-expression database from a variety of human brain samples ranging from before birth to over 80 years in age. Colantuoni et al . focus on the prefrontal cortex. Although they note significant expression pattern dynamics throughout development, they identify a consistent molecular architecture of transcription across subjects from different races despite the large number of genetic polymorphisms among them. Kang et al . produce a more comprehensive time course, exploring expression in 16 different brain areas, determining that the largest spatiotemporal variability occurs before birth, with transcriptomes in brain regions converging as we age. Previous investigations have combined transcriptional and genetic analyses in human cell lines 1 , 2 , 3 , but few have applied these techniques to human neural tissue 4 , 5 , 6 , 7 , 8 . To gain a global molecular perspective on the role of the human genome in cortical development, function and ageing, we explore the temporal dynamics and genetic control of transcription in human prefrontal cortex in an extensive series of post-mortem brains from fetal development through ageing. We discover a wave of gene expression changes occurring during fetal development which are reversed in early postnatal life. One half-century later in life, this pattern of reversals is mirrored in ageing and in neurodegeneration. Although we identify thousands of robust associations of individual genetic polymorphisms with gene expression, we also demonstrate that there is no association between the total extent of genetic differences between subjects and the global similarity of their transcriptional profiles. Hence, the human genome produces a consistent molecular architecture in the prefrontal cortex, despite millions of genetic differences across individuals and races. To enable further discovery, this entire data set is freely available (from Gene Expression Omnibus: accession GSE30272; and dbGaP: accession phs000417.v1.p1) and can also be interrogated via a biologist-friendly stand-alone application ( http://www.libd.org/braincloud ).